Effects of Food and Temperature on The Lipid Accumulation Strategy of Arctic Copepods: Experimental Approach ... - Jonasdottir, Sigrun; Broughton, Richard (Zenodo, 2024)
In an experimental setup, we investigated the effect of food type, temperature and salinity on the lipid accumulation and wax ester type of Calanus finmarchicus copepodites. ...